Characteristics of carbonaceous aerosols emitted from peatland fire in Riau, Sumatra, Indonesia (2): Identification of organic compounds. (June 2015) - Fujii, Yusuke; Kawamoto, Haruo; Tohno, Susumu; Oda, Masafumi; Iriana, Windy; Lestari, Puji
Abstract: Smoke emitted from Indonesian peatland fires has caused dense haze and serious air pollution in Southeast Asia such as visibility impairment and adverse health impacts. To mitigate the Indonesian peatland fire aerosol impacts, an effective strategy and international framework based on the latest scientific knowledge needs to be established. Although several attempts have been made, limited data exist regarding the chemical characteristics of peatland fire smoke for the source apportionment. In order to identify the key organic compounds of peatland fire aerosols, we conducted intensive field studies based on ground-based and source-dominated sampling of PM2.5 in Riau Province, Sumatra, Indonesia, during the peatland fire seasons in 2012. Levoglucosan was the most abundant compound among the quantified organic compounds at 8.98 ± 2.28% of the PM2.5 mass, followed by palmitic acid at 0.782 ± 0.163% and mannosan at 0.607 ± 0.0861%. Potassium ion was not appropriate for an indicator of Indonesian peatland fires due to extremely low concentrations associated with smoldering fire at low temperatures. The vanillic/syringic acids ratio was 1.06 ± 0.155 in this study and this may be a useful signature profile for peatland fire emissions. Particulate n -alkanes also have potential for markers to identify impact of Indonesian peatland fire source at a receptor site. Highlights: Organic compounds in PM2.5 emitted from peatland fires were characterized. Potassium cannot be used as a source indicator for peatland fires. We found some potential source indicators of peatland fire.